Spatial memory: behavioural determinants of persistence in the watermaze delayed matching-to-place task - da Silva, Bruno M.; Bast, Tobias; Morris, Richard G.M. (Cold Spring Harbor Laboratory Press, 2014)
The watermaze delayed matching-to-place (DMP) task was modified to include probe trials, to quantify search preference for the correct place. Using a zone-analysis of search-preference, a gradual decay of one-trial memory in rats was observed over 24 h with weak memory consistently detected at a retention interval of 6 h, but unreliably at 24 h. This forgetting function in the watermaze was similar to that found using a search-preference measure in a food-reinforced dry-land DMP task (Bast et al. 2005). In a search for strong and weak encoding conditions, essential for a later behavioral tagging study, three encoding trials gave strong 6-h and 24-h memory when trials were separated by 10 min (spaced training) but not 15 s (massed training). The use of six encoding trials gave good 6-h memory with both spaced and massed training. With respect to weak encoding, placement on the escape platform, instead of the rat swimming to it, resulted in detectable memory at 30 min but this had faded to chance within 24 h. In contrast to the search-preference measure, latencies to cross the correct place neither revealed the gradual forgetting of place memory nor the benefit of spaced training.